Real-time analysis of dual-display phage immobilization and autoantibody screening using quartz crystal microbalance with dissipation monitoring - Rajaram K (Dove Medical Press, 2015)
Kaushik Rajaram,1 Patricia Losada-Pérez,2,3 Veronique Vermeeren,1 Baharak Hosseinkhani,1 Patrick Wagner,2,4 Veerle Somers,1 Luc Michiels1 1Biomedical Research Institute (BIOMED), Hasselt University, Hasselt, 2Institute for Materials Research (IMO), Hasselt University, 3IMEC vzw, Division IMOMEC, Diepenbeek, 4Soft Matter and Biophysics Section, Department of Physics and Astronomy, KU Leuven, Leuven, Belgium Abstract: Over the last three decades, phage display technology has been used for the display of target-specific biomarkers, peptides, antibodies, etc. Phage display-based assays are mostly limited to the phage ELISA, which is notorious for its high background signal and laborious methodology. These problems have been recently overcome by designing a dual-display phage with two different end functionalities, namely, streptavidin (STV)-binding protein at one end and a rheumatoid arthritis-specific autoantigenic target at the other end. Using this dual-display phage, a much higher sensitivity in screening specificities of autoantibodies in complex serum sample has been detected compared to single-display phage system on phage ELISA. Herein, we aimed to develop a novel, rapid, and sensitive dual-display phage to detect autoantibodies presence in serum samples using quartz crystal microbalance with dissipation monitoring as a sensing platform. The vertical functionalization of the phage over the STV-modified surfaces resulted in clear frequency and dissipation shifts revealing a well-defined viscoelastic signature. Screening for autoantibodies using antihuman IgG-modified surfaces and the dual-display phage with STV magnetic bead complexes allowed to isolate the target entities from complex mixtures and to achieve a large response as compared to negative control samples. This novel dual-display strategy can be a potential alternative to the time consuming phage ELISA protocols for the qualitative analysis of serum autoantibodies and can be taken as a departure point to ultimately achieve a point of care diagnostic system. Keywords: dual-display phage, surface plasmon resonance, quartz crystal microbalance, dissipation monitoring, streptavidin-binding protein, rheumatoid arthritis